2013
DOI: 10.3109/10520295.2013.780635
|View full text |Cite
|
Sign up to set email alerts
|

Predicting small molecule fluorescent probe localization in living cells using QSAR modeling. 2. Specifying probe, protocol and cell factors; selecting QSAR models; predicting entry and localization

Abstract: We describe the practical issues and the methodological procedures that must be carried out to construct and use QSAR models for predicting localization of probes in single cells. We address first the determination of probe factors starting with a consideration of the chemical nature of probe molecules present. What is their identity? Do new compounds arise in incubation media or intracellularly? For each probe, how many distinct chemical species are present? For each probe species, the derivation of the follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 25 publications
1
35
0
1
Order By: Relevance
“…Through cell imaging experiments, we confirmed that only IMT could stain DNA G-quadruplexes in the nucleus, while other probes mainly stain nucleoli. Differences in the localization of these probes within the cells may involve a variety of factors (58,59), such as the water/octanol partition coefficient (log P ), substituent bulk parameter and differential fluorescence identification of DNA and RNA G-quadruplexes. IMT is almost non-fluorescent before binding to a target molecule or after binding to single/double-stranded nucleic acids, but exhibits over 200-fold fluorescence enhancement after binding with G-quadruplexes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Through cell imaging experiments, we confirmed that only IMT could stain DNA G-quadruplexes in the nucleus, while other probes mainly stain nucleoli. Differences in the localization of these probes within the cells may involve a variety of factors (58,59), such as the water/octanol partition coefficient (log P ), substituent bulk parameter and differential fluorescence identification of DNA and RNA G-quadruplexes. IMT is almost non-fluorescent before binding to a target molecule or after binding to single/double-stranded nucleic acids, but exhibits over 200-fold fluorescence enhancement after binding with G-quadruplexes.…”
Section: Resultsmentioning
confidence: 99%
“…Since IMT does not show a significant difference in fluorescence after binding to the G-quadruplex structures of DNA and RNA, theoretically the fluorescence foci derived from the labeling of RNA G-quadruplexes should be observed in the cytoplasm. According to the quantitative structure activity relations (QSAR) models (58,59), the physicochemical characteristics of a probe molecule determine its localization within the cells. As a permanent cationic species, the physicochemical characteristics of IMT make it more likely to localize to the nuclear chromatin rather than the cytoplasm.…”
Section: Resultsmentioning
confidence: 99%
“…For each species, structure parameter values, as estimated above, were inserted into published QSAR models predicting cell uptake and intracellular localizations. [22] The poor-moderate-good predictions in Tables S1, S3 and S5 in the supporting information relate to the log P of the major species present, usually the free base, as follows:…”
Section: Methodsmentioning
confidence: 99%
“…Thus, when the values of certain physicochemical properties of a dye are available (see [98] for procedures), and are expressed as numerical structure parameters (AI, CBN, HGH, HGS, LCF, log P, pK a , SB, W/L, Z), then insertion of these values into simple QSAR models (see [40] for a summary) allows the prediction of dye exclusion from, or uptake into, living eukaryotic cells. Similarly, if dye uptake into live cells occurs, then additional simple QSAR models, summarised in [40], can predict many subcellular dye accumulation sites (e.g.…”
Section: Conclusion Critiques and Future Directionsmentioning
confidence: 99%